Advances in measurable residual disease monitoring for adult acute lymphoblastic leukemia. Issue 4 (6th June 2019) - Meleveedu, Kapil Sankar; Litzow, Mark
Abstract: Adult acute lymphoblastic leukemia management has traditionally relied upon pretreatment conventional risk factors for treatment decisions. Despite using intensive multiagent chemotherapy followed by a prolonged maintenance or allogeneic stem cell transplantation, these patients remain at a high risk of relapse. Improved techniques for detection of measurable residual disease (MRD) have tremendously changed the posttreatment disease burden assessment and evolved as a powerful predictor of relapse and survival superseding historical prognostic factors. Moreover, MRD measurement has become an integral part of risk stratification, prognosis assessment, intensification or de‐escalation of treatment, monitoring of disease burden, and an endpoint in clinical trials. With existing approaches like allogeneic hematopoietic stem cell transplantation and emergence of novel agents (eg, blinatumomab, inotuzumab ozogamicin, and chimeric antigen receptor [CAR] T cells) that are highly effective in eradicating residual disease, understanding the role of MRD in treatment decisions is getting more and more important and complex. This review will highlight the advances that have been achieved in MRD monitoring over the years and the practical applications in different time points of treatment to provide a framework for rational management decisions by practicing hematologists and oncologists.